The Contemporary Status of Pingxian Folk Songs and Their Educational Significance in Qinghai Province Through Anthropological Analysis - Yang, Jing; Theerapan, Suthasinee (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: This anthropological study delves into the contemporary status and educational significance of Pingxian folk songs in Qinghai Province, China. Pingxian folk songs are known for their delicate melodies. This research aims to analyze the contemporary status of Pingxian folk songs in Qinghai Province and their educational significance through anthropological analysis. Materials and Methods: The research is situated primarily in Qinghai Province, specifically focusing on Xining City, a central hub of Pingxian folk songs. Data collection involves in-depth interviews and systematic observation of performances, facilitated by structured interviews and observation forms. Four key informants, including local musicians, community elders, and music educators. Results: These songs have transitioned from local folk art to distinct local folk music, embracing diverse musical elements and the emergence of professional troupes. They continue to thrive through regular performances, preserving local dialects, and enchanting melodies, and serving as living repositories of history and culture. Furthermore, Pingxian folk songs play a pivotal role in fostering cultural identity, nurturing creativity, and enhancing social cohesion among learners, contributing to cultural heritage protection and the rejuvenation of Chinese traditions. Conclusion: Pingxian folk songs in Qinghai Province epitomize a dynamic cultural heritage that resonates with audiences today. Their enduring legacy, enriched by historical evolution and contemporary vitality, underscores their significance in education and cultural preservation. As valuable tools for instilling cultural identity and fostering creativity.